Religions with or without Sense of Humor: A Psychological Perspective - Prieto, José M. (Religions, 2021)
The contrast between Homo Ridens and Homo Religiosus is launched and followed by the tug of war between the laugh of God and the sin of laughter. Funniness in jokes with religious content is explored through the incongruity-resolution model developed by Suls, a psychologist expert in artificial intelligence: among the faithful abound believers whom it deems inappropriate the hilarious endings invented, with ulterior motives, by humorists. The transgression model in graphic design, elaborated by Alvarez Junco, provides the frame of reference to discern the camouflage of four frescos and a sculpture by Michelangelo, who knew more than he appeared, and was a dissident, but not a heretic. Humor cannot be reduced to jokes, and the taxonomy created by Long and Grasser (cognitive and experimental psychologists) has been used to accentuate the nexus between witticism in daily life interactions with religious connotations: their eleven categories have been portrayed using literary narratives authored by well-known European and Asian writers. Efforts have been made to draft them with the sense of humor that corresponds to the heading. Psychologists pay attention mainly to individual or group experiences, that is, religiosity. Artists have relied on camouflage to ensure that inquisitive persons do not react by penalizing.